A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae) - Snyman, Louwrens P.; Sole, Catherine L.; Ohl, Michael (Zootaxa, 2018)
The Mantispinae (Neuroptera: Mantispidae) genera of the Oriental and Palearctic regions are revised. A morphological key to the genera is generated. Austroclimaciella, Campancella, Mantispa, Mantispilla, Necyla, Stenomantispa and Tuberonotha are redescribed. The Ohl (2004) catalogue is updated for the relevant genera. Sagittalata (= Perlamantispa) is assigned as a synonym of Mantispilla which is restored as a valid genus. Orientispa is assigned as a synonym of Necyla.